2021
DOI: 10.21776/ub.ijabs.2021.29.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Sharia Supervisory Board (Ssb) in Moderating the Effect of Good Corporate Governance on Financial Performance of Islamic Banks in Indonesia

Abstract: Purpose — The aims of this research are to examine and analyze the extent of the role of the sharia supervisory board (SSB) in moderating the effect of good corporate governance on the financial performance of Islamic banks in Indonesia. Design/methodology/approach — The population in this research is 14 (fourteen) Islamic banks in Indonesia and the sample used in this research is 9 (nine) Islamic banks that have published financial reports, good corporate governance reports, and annual reports for the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Another possibility is that the company will focus more on increasing ROA, if social disclosure requires expensive costs, and it is not company-centric in increasing its profits. Companies will focus more on cost efficiency that does not have a direct effect on investors such as non-financial disclosures such as ISR (Siswanti et al, 2021) In the point of view of stakeholder theory, many companies have reported CSR as a form of their business strategy, as well as sharia business actors who are required to report their social responsibility activities, this will generate stakeholder trust and indirectly this can improve performance (Jihadi et al, 2021). This is very contrary to stakeholder theory.…”
Section: Financial Performance and Isrmentioning
confidence: 95%
“…Another possibility is that the company will focus more on increasing ROA, if social disclosure requires expensive costs, and it is not company-centric in increasing its profits. Companies will focus more on cost efficiency that does not have a direct effect on investors such as non-financial disclosures such as ISR (Siswanti et al, 2021) In the point of view of stakeholder theory, many companies have reported CSR as a form of their business strategy, as well as sharia business actors who are required to report their social responsibility activities, this will generate stakeholder trust and indirectly this can improve performance (Jihadi et al, 2021). This is very contrary to stakeholder theory.…”
Section: Financial Performance and Isrmentioning
confidence: 95%
“…However, in a similar study, Hamsyi (2019) reported contradictory results as he found a significant positive correlation between Islamic income ratio and profitability and insignificant correlation between profit sharing ratio and profitability. Siswanti et al (2021) found that the impact of Islamic income ratio on profitability is moderated by corporate social performance. On the other hand, Alam et al (2022) found that Shariah Supervisory Board management had a positive relationship with Shariah compliance and bank reputation.…”
Section: Impact Of Shariah Compliance On Financial Performancementioning
confidence: 99%
“…On the other hand, the company's financial performance is an important instrument in decision-making by investors. The effectiveness of company finances results from management activities (Siswanti et al, 2021). To assess the success of company management in achieving company goals set within a certain period, using the results of management activities as parameters or benchmarks.…”
Section: Introductionmentioning
confidence: 99%